Development of a preoperative prediction model for new-onset diabetes mellitus after partial pancreatectomy: A retrospective cohort study. Issue 24 (18th June 2021) - Yamamoto-Kataoka, Sachiko; Shimizu, Sayaka; Yamazaki, Hajime; Murakami, Katsuhiro; Nishizaki, Daisuke; Fukuhara, Shunichi; Inagaki, Nobuya; Yamamoto, Yosuke
Abstract : Abstract: Pancreatectomy is an invasive surgery that is sometimes associated with complications. New-onset diabetes mellitus sometimes develops after partial pancreatectomy and severely affects the patient's quality of life. This study aimed to develop a preoperative prediction model of new-onset diabetes mellitus after partial pancreatectomy, which will help patients and surgeons to achieve more easily better common decisions on regarding whether to perform partial pancreatectomy. This retrospective cohort study analyzed medical records of patients who underwent partial pancreatectomy (total pancreatectomy excluded) from April 1, 2008, to February 28, 2016, which were available in the database provided by Medical Data Vision Co., Ltd. (Tokyo, Japan). The predictors were preoperative age, body mass index, hemoglobin A1c level, blood glucose level, and indication for partial pancreatectomy. The outcome was the development of new-onset diabetes mellitus at 1 to 12 months after partial pancreatectomy. We used a logistic regression model and calculated the scores of each predictor. To determine test performance, we assessed discrimination ability using the receiver operating characteristic curve and calibration with a calibration plot and the Hosmer-Lemeshow test. We also performed internal validation using the bootstrap method. Of 681 patients, 125 (18.4%) had new-onset diabetes mellitus after partial pancreatectomy. The developed prediction model had a possible range of 0 to 46 points. The median score was 13, and the interquartile range was 9 to 22. The C-statistics of the receiver operating characteristic curve on the score to predict the outcome was .70 (95% confidence interval [CI], .65–.75). Regarding the test performance, the Hosmer-Lemeshow test was not significant ( P  = .17), and calibration was good. In the bootstrapped cohorts, the C-statistics was .69 (95% CI, .62–.76). We developed a preoperative prediction model for new-onset diabetes mellitus after partial pancreatectomy. This would provide important information for surgeons and patients when deciding whether to perform partial pancreatectomy. Abstract : Supplemental Digital Content is available in the text